Concern In Lung Cancer In John Green's The Fault In Our Stars Novel (2012) : A Reader Response Theory - APRINTYA, Esa Kartika, Dr. M. Thoyibi, M.S (2017)
This research is about the readers' concern towards the issue of lung cancer in the novel The Fault in Our Stars (2012) which was analyzed based on Reader-Response theory. The aims of this study was to identified the major issues responded by the readers', described how the readers' response towards the issue lung cancer, and to analyzed the readers' response related to their background. The primary data source was the readers' reviews data on the Goodreads website. The secondary data of this study was from others source which related with this study such as, journal/e-journal, e-book, books, dictionary and some website that support this study. This study comes to the following conclusion. First, there were 10 major issues responded by the readers'; Second, the readers' was given both of the positive reviews and negative reviews towards lung cancer. The third results were show that there was relation between the readers' response with their background.